2013
DOI: 10.1016/j.molcel.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

SIRT6 Recruits SNF2H to DNA Break Sites, Preventing Genomic Instability through Chromatin Remodeling

Abstract: Summary DNA damage is linked to multiple human diseases, such as cancer, neurodegeneration and senescence. Little is known about the role of chromatin accessibility in DNA repair. Here, we find that the histone deacetylase SIRT6 is one of the earliest factors recruited to sites of Double-Strand Breaks (DSBs). SIRT6 recruits the ISWI-chromatin remodeler SNF2H to DSBs, and deacetylates focally histone H3K56. Lack of SIRT6 and SNF2H impairs chromatin remodeling, increasing sensitivity to genotoxic damage and recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
319
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 335 publications
(350 citation statements)
references
References 45 publications
17
319
0
1
Order By: Relevance
“…We, as well as other groups, reported that the chromatin remodeling factor SNF2h/SMARCA5 is recruited to DSB damage sites induced by laser micro-irradiation (Nakamura et al, 2011;Toiber et al, 2013;Vidi et al, 2014). We also found that depletion of RNF20 reduced H2B ubiquitination-mediated methylation (H3-K4) and accumulation of SNF2h at DSB sites, suggesting that RNF20-dependent ubiquitination of H2B and H3 methylation are crucial for the recruitment of SNF2h to DSB sites.…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…We, as well as other groups, reported that the chromatin remodeling factor SNF2h/SMARCA5 is recruited to DSB damage sites induced by laser micro-irradiation (Nakamura et al, 2011;Toiber et al, 2013;Vidi et al, 2014). We also found that depletion of RNF20 reduced H2B ubiquitination-mediated methylation (H3-K4) and accumulation of SNF2h at DSB sites, suggesting that RNF20-dependent ubiquitination of H2B and H3 methylation are crucial for the recruitment of SNF2h to DSB sites.…”
Section: Introductionsupporting
confidence: 74%
“…Depletion of SUPT16H caused similar defects to those observed in RNF20-deficient cells regarding chromatin accumulation of RNF20, IR-induced focus formation of HR-related factors (BRCA1 and RAD51) and HR activity, suggesting that SUPT16H plays a key role in RNF20-dependent DDRs through its interactions. Depletion of SIRT6, a histone deacetylase, reduced RNF20 recruitment to DSB sites and also H2B K120 ubiquitination (Toiber et al, 2013;Vidi et al, 2014). Accumulation of RNF20 may be regulated by its histone acetylation status as well as its interaction with NBS1 and SNF2h.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, SIRT1 is an apical effector involved in the stabilization of ATM at DNA breaks, which is essential for DDR propagation (Dobbin et al , 2013). SIRT6 also participates in the early events of DDR, as indicated by its rapid accumulation at DNA damage sites, where it recruits the chromatin remodeler SNF2H and focally deacetylates histones H3K56 (Toiber et al , 2013) and H3K9 (McCord et al , 2009). In addition, SIRT6 depletion impairs the recruitment of downstream effectors from both NHEJ and HR repair pathways to DSB (Kaidi et al , 2010; Toiber et al , 2013).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT6 also participates in the early events of DDR, as indicated by its rapid accumulation at DNA damage sites, where it recruits the chromatin remodeler SNF2H and focally deacetylates histones H3K56 (Toiber et al , 2013) and H3K9 (McCord et al , 2009). In addition, SIRT6 depletion impairs the recruitment of downstream effectors from both NHEJ and HR repair pathways to DSB (Kaidi et al , 2010; Toiber et al , 2013). Our results indicate that SIRT7 is located downstream of SIRT1 and SIRT6 in the DNA damage signaling cascade.…”
Section: Discussionmentioning
confidence: 99%